2009
DOI: 10.1097/rli.0b013e318198a0ae
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of 1.0 M Gadobutrol and 0.5 M Gadopentetate Dimeglumine-Enhanced Magnetic Resonance Imaging in Five Hundred Seventy-Two Patients With Known or Suspected Liver Lesions

Abstract: This study documents evidence for the noninferiority of a single i.v. bolus injection of 1.0 M gadobutrol (0.1 mmol/kg body weight) to 0.5 M gadopentetate (0.1 mmol/kg body weight) in the diagnostic assessment of liver lesions with contrast-enhanced MRI. The known excellent safety profile of gadobutrol was confirmed in this clinical trial and is similar to that of gadopentetate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
25
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 41 publications
2
25
0
Order By: Relevance
“…In abdominal dynamic MR angiography gadobutrol has superior contrast compared with 0.5 M GBCA [20]. Some publications report the use of gadobutrol for indications other than in CNS imaging and MR angiography [21,22]. Until now, no one has evaluated this Gd chelate in a direct comparison to another contrast agent for musculo-skeletal imaging purposes.…”
Section: Discussionmentioning
confidence: 97%
“…In abdominal dynamic MR angiography gadobutrol has superior contrast compared with 0.5 M GBCA [20]. Some publications report the use of gadobutrol for indications other than in CNS imaging and MR angiography [21,22]. Until now, no one has evaluated this Gd chelate in a direct comparison to another contrast agent for musculo-skeletal imaging purposes.…”
Section: Discussionmentioning
confidence: 97%
“…The PK profile of 0.1 mmol/kg gadobutrol in children 0 to aged younger than 2 years is similar to that determined in other populations (pediatric population 2 years and older and adults), characterized by a rapid decline in plasma concentrations after injection reflecting the distribution into the extracellular space and fast elimination from the body by glomerular filtration. 11,15 Because gadobutrol is cleared by glomerular filtration, age-related adaptations in renal function, in addition to BW in very young children, are expected to influence the PK of gadobutrol. This expected difference in clearance was adequately described by including the covariate age on CL in the PK analyses.…”
Section: Discussionmentioning
confidence: 99%
“…[13][14][15][16][17][18] Because of its macrocyclic structure, gadobutrol has a high stability 19 and a clinically proven safety profile in adults and children. 20 Mainly due to its macrocyclic structure and high stability, gadobutrol has been assigned to the low-risk group according to the European Committee for Medicinal Products for Human Use and the Food and Drug Administration classifications.…”
mentioning
confidence: 99%
“…Only a few studies have reported on the performance of double-blinded studies to ensure the fair evaluation of both currently used and potential new agents [7,22]. This study describes the first report of performing this evaluation using GBCAs with adverse events as the primary end point.…”
Section: Discussionmentioning
confidence: 96%
“…A variety of GBCAs are available in the United States, with more agents also in the process of FDA evaluation [5]. Critical to the decision whether to employ a new contrast agent in an imaging department is how it compares to the currently employed contrast agent [6,7]. The traditional method of evaluating contrast agents is to perform a trial of using the new agent in a predefined number of patients, often based on the number of samples that the local sales representative provides.…”
Section: Introductionmentioning
confidence: 99%